Comparative concepts of justice in Islamic and Western legal-political thought : a dual heritage affecting gender justice in Malaysia - Nik Noriani Nik Badli Shah
This dissertation proposes to look into certain concepts of justice from comparative Islamic and Western perspectives in legal-political thought, with a view of their historical developments in relation to their contemporary relevance. In recent decades, there have been calls both for the revival and preservation of Islamic systems and institutions, and for modernization and reform. Since both Islamic and Western influences play significant roles in the development of legal status in Malaysia, a comparative study would be useful in looking at similarities as well as differences, for instance it is possible to find common ground between some Western ideas on representative government with Islamic concepts on shura or consultation. Modem forms of representative government have been influenced by revolutionary upheavals as well as evolutionary developments. An understanding of Islamic theology and philosophy demonstrates the underlying bases of Islamic jurisprudence, and the intertwining of theological debates on justice with political notions. Western theories on law and justice, including classical positivism and natural law theories, and comparisons with Islamic legal theory on positive law in ideal form, will be discussed. Ideas of certain major thinkers in Islamic reformism and revivalism will be included, such as the modernist movement of Sheikh Muhammad 'Abduh of Egypt, reflected in Malaya by Syed Shaykh al-Hady. Ideas of certain major thinkers in Western civilization, such as Locke and Rousseau, also influenced the historical developments of political and legal systems. Subordination of women in the West prior to the 20th century will illustrate that women's rights were neither inherently nor exclusively part of Western traditions. Confusion may occur when practices of one culture are mistaken for another, for instance when Victorian values are mistaken for Islamic principles. Orientalists have conducted studies on Islamic civilization from their perspective; thus Muslims should also conduct studies on Western civilizations from our perspective. The dual heritage in Malaysia is reflected in its dual legal system. Chinese and Hindu customary laws also used to be significant, but are no longer so since the Law Reform (Marriage and Divorce) Act 1976 was enforced upon nonMuslims. Family laws have become a main dividing line between Muslims and others, as though necessarily incompatible and mutually exclusive. However, the discussion will show that areas of English family law have benefited from Islamic family law to the advantage of women, especially regarding married women's property rights and child custody. It is unfortunate that contributions to gender justice from Islamic law are unrecognized and ignored. Instead, there is popular misconception that gender justice is based on Western civilizations.